Shareholder Activism Benefits and Drawbacks - Hartmann, Marion; Hartmann, Marion (Peter Lang, 2014)
This book analyses and compares the benefits and drawbacks of shareholder activism in corporations under US American and German law, applying means of new institutional economics. The analysis concentrates on three fields of action of active shareholders in targeted corporations: nominations and elections, transaction decisions and financial decisions. The author evaluates and compares the effectiveness of the means which active shareholders use and of the limitations they face. She concludes that shareholder activism has benefits and drawbacks. Both require legal actions under the two jurisdictions, such as stronger nomination and election rights under US American law and more effective disclosure obligations under German law.